Vibronic coherence evolution in multidimensional ultrafast photochemical processes - James D. Gaynor (Nature Portfolio, 2019)
Energy transfer in light harvesting complexes involves electronic, vibrational, and vibronic couplings which are challenging to resolve. Here the authors observe the time-evolution of vibronic coherences driving charge transfer in a photoexcited solvated transition metal complex by two- and three-dimensional electronic-vibrational spectroscopy.